Membangun Kehidupan yang Berkah, Tauhid sebagai Sumber Motivasi - Rizky Ari Prastyo; Aji Tiranto; Wira Abdi; Marcelino Marcelino (Reflection : Islamic Education Journal, 2025)
Building a blessed life is a goal that is aspired by many individuals in society. In this context, tawhid as a single divine concept becomes an important source of motivation. This study aims to explore how understanding tawhid can influence individual attitudes and behaviors in building a blessed life. Through a qualitative approach, this study collected data from in-depth interviews with a number of respondents who have a strong understanding of tawhid. The methods used in this study are using a Qualitative approach, In-depth Interviews, Thematic Analysis, Research Results, Internalization of Tawhid, Positive Attitudes, Moral Behavior, and Social Contribution. The results of the study show that individuals who internalize the concept of tawhid tend to have a more positive perspective on life, and are able to overcome various challenges better. They feel inner peace and strong motivation to contribute to the surrounding environment. In the data analysis, it was found that tawhid not only functions as a spiritual belief, but also as a moral foundation that directs individuals to behave well. Respondents expressed that this belief motivated them to prioritize honesty, hard work, and helping each other in the community. This indicates that tawhid plays a significant role in shaping positive character and mindset. The conclusion of this study emphasizes the importance of integrating the values ​​of monotheism in education and community development. By building awareness of the concept of monotheism, it is hoped that society can achieve a blessed, harmonious, and sustainable life. This study is expected to be a reference for stakeholders in creating programs that support the strengthening of spiritual values ​​in society.